The Design of Microstrip Antena With Peripheral Slits For Digital Tv Application - Alam, Syah; Kholis, Ikhwannul (Teknik dan Ilmu Komputer, 2016)
AbstrakÃÂ Dalam paper ini dibahas tentang antena mikrostrip yang dirancang untuk aplikasi TV Digital (DVB T2) pada frekuensi kerja 586 MHz dengan menggunakan metode peripheral slits. Metode peripheral slits digunakan untuk membuat ukuran antena menjadi lebih kecil dan compact sehingga dapat digunakan untuk aplikasi TV Digital DVB T2 untuk kondisi dalam gedung (indoor). Antena yang didesain memiliki bentuk patch segiempat yang diberi beban beberapa slit untuk dapat membuat antena menjadi kecil. Bahan substrat yang digunakan pada perancangan antena ini adalah FR 4 Epoxy yang memiliki nilai konstanta dielektrik (Ãâr) = 4,3 dengan ketebalan bahan (h) 1,53 mm. Dari hasil simulasi dengan bantuan perangkat lunak diperoleh nilai return loss -18,56 dB dengan nilai VSWR 1,269.ÃÂ Kata Kunci: Microstrip, antena, return loss, VSWR, return loss, peripheral slits, patchÃÂ ÃÂ AbstractÃÂ This paper discussed about the microstrip antenna designed for the Digital TV (DVB T2) application at the working frequency of 586 MHz using peripheral slits. The peripheral slits method was used to make the antenna size smaller and compact so it could be used for the DVB T2 Digital TV applications in the building (indoor). The antenna design was a rectangular patch which was loaded with the multiple slit to make the antenna small. The substrate materials used in the design of this antenna was Epoxy FR 4 that had a dielectric constant values (Ãâr) = 4.3 with the material thickness ( h ) of 1.53 mm. The result obtained from the simulation with the help of software was the return loss value of -18.56 dB and the VSWR value of 1.269.ÃÂ Keywords: WiMAX, Triangular, Microstrip, Antena, Return Loss, VSWRÃÂ ÃÂ